Perivascular Macrophages Are the Primary Cell Type Productively Infected by Simian Immunodeficiency Virus in the Brains of Macaques: Implications for the Neuropathogenesis of AIDS - Williams, Kenneth C. (The Rockefeller University Press, 2001)
The macrophage is well established as a target of HIV and simian immunodeficiency virus (SIV) infection and a major contributor to the neuropathogenesis of AIDS. However, the identification of distinct subpopulations of monocyte/macrophages that carry virus to the brain and that sustain infection within the central nervous system (CNS) has not been examined. We demonstrate that the perivascular macrophage and not the parenchymal microglia is the primary cell productively infected by SIV. We further demonstrate that although productive viral infection of the CNS occurs early, thereafter it is not easily detectable until terminal AIDS. The biology of perivascular macrophages, including their rate of turnover and replacement by peripheral blood monocytes, may explain the timing of neuroinvasion, disappearance, and reappearance of virus in the CNS, and questions the ability of the brain to function as a reservoir for productive infection by HIV/SIV.